16. Dinamika Kerjasama Littoral States dan User States dalam Penanganan Kasus Perompakan Kapal: Studi Kasus Selat Malaka dan Selat Singapura (2010-2014) - Iffah Permata Sari; Tri Cahyo Utomo; Satwika Paramasatya (Journal of International Relations Diponegoro, 2017)
Malacca and Singapore straits are among the world’s most important SLOC (Sea Lines ofCommunication) and SLOT (Sea Lines of Trade) which categorized as armed robberyprone areas. Based on UNCLOS art. 43, littoral states and user states should cooperate toovercome this issue. On the other hand, they have different interests in Malacca andSingapore straits. This research discuss the different interest between littoral states anduser states and how it effects the dynamic cooperation on combating armed robberyagainst ship in Malacca and Singapore Straits from 2010 to 2014. This study found thatthe different interest between those countries effected the cooperation on combating armedrobbery. Furthermore, it also influence the main purpose and activities of the cooperation.The dynamic cooperation between littoral states and user states emerges on multilateral,trilateral, and bilateral cooperation. This research is carried out by using descriptiveanalysisand qualitative method. This study incorporates the framework of internationalcooperation theory to observe the dynamic cooperation as the conceptual basis of theresearch.